Covid-19 pandemic impact on mental health: a web-based cross-sectional survey on a sample of Italian general practitioners - Amerio, Andrea; Bianchi, Davide; Santi, Francesca; Costantini, Luigi; Odone, Anna; Signorelli, Carlo; Costanza, Alessandra; Serafini, Gianluca; Amore, Mario; Aguglia, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Background: Since the World Health Organization declared the new 2019 coronavirus disease (Covid-19) outbreak first a Public Health Emergency of International Concern and then a pandemic, Italy held more than 195.350 cases and 26.380 deaths. Working in the frontline with suspected Covid-19 infection patients, general practitioners (GPs) are daily under both physical and psychological pressure.  Methods: A web-based cross-sectional survey was carried out on italian GPs working in Genoa (Italy), to assess the impact of Covid-19 pandemic on mental health. The survey was anonymous and a free Google Forms® software was used. Results: One hundred thirty-one GPs completed the survey. Compared to GPs with absent or mild depressive symptoms (PHQ-9 < 10), GPs reporting moderate to severe depressive symptoms (N=30, 22.9%; PHQ-9 ≥ 10) reported more helplessness (96.7% vs. 79.2%, p=.025), spent more than three hours searching for COVID-19 information (43.3% vs. 19.8%, p=.024), perceived less adequate personal protective equipment (PPE) (6.7% vs. 23.8%, p=.049) and visited more COVID-19 infected patients (16.63 ± 27.30 vs. 9.52 ± 11.75, p=.041). Moreover, PHQ-9 ≥ 10 GPs reported a significant higher severity for both anxiety and insomnia (13.43 ± 4.96 vs. 4.88 ± 3.53 and 11.60 ± 5.53 vs. 4.84 ± 3.81, respectively; p